The social stigma of unemployment: consequences of stigma consciousness on job search attitudes, behaviour and success - Gerhard Krug; Katrin Drasch; Monika Jungbauer-Gans (Journal for Labour Market Research, 2019)
Studies show that the unemployed face serious disadvantages in the labour market and that the social stigma of unemployment is one explanation. In this paper, we focus on the unemployed's expectations of being stigmatized (stigma consciousness) and the consequences of such negative expectations on job search attitudes and behaviour. Using data from the panel study 2Labour Market and Social Security" (PASS), we find that the unemployed with high stigma consciousness suffer from reduced well-being and health. Regarding job search, the stigmatized unemployed are more likely to expect that their chances of re-employment are low, but in contrast, they are more likely to place a high value on becoming re-employed. Instead of becoming discouraged and passive, we find that stigmatized unemployed individuals increase their job search effort compared to other unemployed individuals. However, despite their higher job search effort, the stigma-conscious unemployed do not have better re-employment chances.
Keywords: J64; J68; J78; 330; Expectancy-value theory; Job search; Social stigma; Stigma consciousness; Unemployment